Effect of Heat Moisture Treatment (HMT) Duration and Lactic Acid Concentration on the Characteristics of Purple Sweet Potato Flour (Ipomoea batatas L. Poiret) - Nurminabari, Ina Siti; Gozali, Thomas; Ikrawan, Yusep; Hariadi, Hari; Eriningtyas, Fanisa (Open Global Scientific Journal, 2024)
This study aims to determine the effect of heat moisture treatment (HMT) duration and lactic acid concentration on the characteristics of purple sweet potato flour (Ipomoea batatas L. Poiret). The method consisted of two stages, namely preliminary stage to produce control (unmodified) flour and main stage to produce modified flour. The method used was a randomized group design with a factorial pattern of 3 x 3 and 3 replications. The variables used were HMT duration (3, 5, and 7 hours) and lactic acid concentration (200, 400, and 600 ppm). The parameters observed in the main stage were water content, anthocyanin level, swelling power, color, solubility, and flour gelatinization profile or Rapid Visco Analysis (RVA). The results show that HMT duration affected the water content and solubility of the modified purple sweet potato flour. HMT duration of 7 hours and lactic acid concentration of 600 ppm resulted in flour anthocyanin level of 24.046 mg/kg. The gelatinization profile shows that the modified purple sweet potato flour experienced the initial temperature of gelatinization (pasting temperature) at 92.30ºC, peak viscosity at 1,343 cP, hot paste viscosity (hold viscosity) at 362 cP, cold paste viscosity (final viscosity) at 931 cP, breakdown (viscosity stability during heating) at 381 cP, and seatback (changes in viscosity during cooling) at -31 CP.